Thank You to Our 2024 Peer Reviewers - Stephen M. Griffies; Jiwen Fan; Yuanyuan Huang; Natasha MacBean; Tapio Schneider (Journal of Advances in Modeling Earth Systems)
Abstract The editors of Journal of Advances in Modeling Earth Systems thank the 1,001 reviewers who provided 1,593 reviews during 2024. Their hard work and insights, typically done anonymously, benefits authors, readers, and the broader science community.